2022
DOI: 10.1111/ddg.14746
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of skin diseases in Germany: systematic review of the current state of research – part 1: cutaneous tumor diseases

Abstract: SummaryEpidemiological data are of great importance for the identification of health care needs, the detection of gaps in care, the development of targeted prevention measures, and for the optimization of resource allocation. The aim of this work was to systematically collect all previously published population‐based epidemiological data on skin diseases in Germany. The present part 1 of the publication series deals with tumor diseases of the skin. The results on non‐infectious (part 2) and infectious skin dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 37 publications
0
12
0
4
Order By: Relevance
“…As far as we are aware, this study is the first ever literature search offering an overview of all available, population‐based publications on the epidemiology of skin diseases in Germany. A discussion on the methods used in this study can be found in part 1 of this publication series [5].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As far as we are aware, this study is the first ever literature search offering an overview of all available, population‐based publications on the epidemiology of skin diseases in Germany. A discussion on the methods used in this study can be found in part 1 of this publication series [5].…”
Section: Discussionmentioning
confidence: 99%
“…The largest number of publications referred to psoriasis and AE. The prevalences of these two dermatoses are markedly lower than, for example, senile lentigo (age spots), covered in part 1 of this publication series [5]. However, regarding the relevance for medical care, the fact that both psoriasis and AE are ‘classic’ chronic‐inflammatory skin diseases associated with pruritus, pain, and stigmatization should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations